Cassava improvement in sub-Saharan Africa: contributions of IITA and its partners - Dixon, A.; Okechukwu, R.U.; Ssemakula, G.N.; Hanna, R.; Thresh, J.M.; Hughes, J.; Ingelbrecht, I.L.; Fregene, Martin A.; Legg, James P.; Mahungu, N.M.; Nweke, F.; Ntawuruhunga, Pheneas; et al. (2008)
Cassava is well recognized for its capacity to address food needs of vulnerable communities in unstable environments in SSA. IITA and colleagues in African NARS, in collaboration with CIAT and ARIs have played leading roles in the development of improved cassava varieties which are disease and pest resistant, early maturing, and high yielding. Through a combination of conventional and new approaches, over 400 cassava genotypes have been developed. The characteristics of the new generation of cassava germplasm broke what had been an apparent yield barrier in cassava improvement increasing yields in many locations by at least 50–100% without the use of fertilizer. The improved germplasm is shared with NARS within the region as specific genotypes or improved seed populations for evaluation and selection under local conditions. Improvement programs in Africa that received these materials have tested them under local conditions, selected varieties that outperform local varieties, and released them to farmers in virtually every major cassava producing country. Today, about 30% of the area cropped with cassava in Africa is planted with improved varieties. Without the introduction of more productive cultivars with multiple diseases and pest resistance, the effective biological control of the cassava mealybug and, to a certain extent, of the green mite, cassava production in SSA would be 50% or less of what it is today. That translates to over 13 million tons of dry cassavayear, enough to meet the calorie requirements of 65 million people. The significant gains in the crop’s output in farmers’ fields are not only contributing to the African diet but also propelling commercialization of the crop. This paper highlights contributions to cassava improvement in SSA since 1970 by IITA and its partners, and suggests areas needing strengthening in the drive to produce better crop varieties for different regions and enduses in Africa.